The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.25139/jsk.v3i3.1882
|View full text |Cite
|
Sign up to set email alerts
|

Moral panics on lgbt issues: evidence from indonesian tv programme

Abstract: There was a discussion activity conducted by a small club of the University of Indonesia called SGRC (Support Group and Resource Center on Sexuality Studies) at the beginning of January 2016. It did not only discuss sexuality such as sexual preferences but also conduct peer support for LGBT groups. However, it was reported illegal for many reasons. Although later the “illegal” stamp was dubbed as an "internal problem" of Universitas Indonesia, the effect was unbelievable. The activity of SGRC was reported by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 17 publications
0
6
0
6
Order By: Relevance
“…Horn et al (2009) state that transgender groups are not a new phenomenon in Indonesia and have formed several community groups. Despite State has an obligation on human rights as stated in Novitsky (2018) and Carozza (2003), however, several pieces of research on discrimination against transgender have been conducted, such as by The Community Legal Aid Institute (LBH Masyarakat) and in Listiorini (2019) found that the transgender people are the victims of sexual orientation-based discrimination and violence.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Horn et al (2009) state that transgender groups are not a new phenomenon in Indonesia and have formed several community groups. Despite State has an obligation on human rights as stated in Novitsky (2018) and Carozza (2003), however, several pieces of research on discrimination against transgender have been conducted, such as by The Community Legal Aid Institute (LBH Masyarakat) and in Listiorini (2019) found that the transgender people are the victims of sexual orientation-based discrimination and violence.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Community Legal Aid Institute (LBH Masyarakat) conducted research throughout 2017 and there were 715 transgender people victims of sexual orientation-based discrimination and violence (Listiorini et al, 2019). During 2014-2019, the Indonesian Lentera Style Color Network (GWL-INA) recorded 24 murder cases against trans women in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Berbagai suguhan pemberitaan terkait kelompok LGBT terus dipertontonkan dan melahirkan homophobia di masyarakat. Pada 2016, sedikitnya ada 9 media yang turut menyebarkan ujaran kebencian kepada kelompok LGBT yang menimbulkan keresahan dan ketakutan, sehingga melahirkan fenomena kepanikan moral (Listiorini et al, 2019). Artinya, yang dianggap normal adalah perilaku heteronormativitas yaitu lelaki yang berpasangan dengan perempuan.…”
Section: Pendapat Masyarakat Mengenai Kelompok Lgbtunclassified
“…Metode pengumpulan data yang digunakan oleh peneliti adalah observasi, wawancara mendalam, studi kepustakaan, dan penelusuran online (Listiorini et al, 2019;Widyaningrum & Nugraheni, 2019;Winarti, 2017). Observasi adalah salah satu teknik pengumpulan data yang tidak hanya mengukur sikap dari responden namun untuk merekam situasi atau kondisi yang terjadi, dilakukan secara sengaja terhadap obyek yang akan diteliti.…”
Section: Metodeunclassified